Analysis of Economic Management Problems and Development Trend of Jixi Coal Enterprises Based on Big Data under Coal Economy Situation. Issue 2 (October 2020) - Zhang, Heming; Yu, Chunyu
Abstract: With the continuous improvement of China's national economy, the economic management based on big data technology of Jixi coal enterprises is no longer a very rare topic. How to provide support for the sustainable development of economic management based on big data technology of coal enterprises and develop economic benefits is an urgent problem for coal enterprises at present. Starting with some problems encountered in the economic management based on big data technology of coal enterprises, this paper puts forward feasible Suggestions for the sustainable development and efficiency improvement of enterprise economic management based on big data technology under the new normal economy, for the reference of readers.